EFFECTS OF LOW DOSE EXPOSURE OF BORAX FOR 8 WEEKS ON GASTRIC ULCER FORMATION - Audi Salman Faza; Linda Dewanti; Ema Qurnianingsih (Majalah Biomorfologi, 2020)
Background: Borax, a carcinogenic toxicant, is illegally used as food additives frequently. Previous researches shown that high dose of borax exposure (300 mg/kg of BW) caused gastric ulcer, but low dose of borax, as found as usual dose in food, has not been frequently researched. Objective: The aim of this study was to analyze the effects of low dose of borax for 8 weeks on the formation of gastric ulcer. Materials and Methods: Twenty four young adult rats (Rattus norvegicus) were divided into 4 groups (Control, Group 1, 2, and 3). Borax doses of 50 mg/kg, 150 mg/kg, and 300 mg/kg were administered on groups 1, 2, and 3 respectively through sonde for 8 weeks; Control group was not exposed with borax. Body weight was monitored every 2 weeks. On the last day of the experiment, rats were euthanized and gastric ulcers were histopathologically analyzed using a microscope. The data were analyzed by the comparative test of Mann-Whitney and the significancy was set on p<0.050. Results: The results showed that body weight was significantly different on the 6th week between Control vs Group 1 (p=0.010) and Control vs Group 3 (p=0.043). The grade of gastric ulcer was found higher in Group 2 and Group 3 compared to Control (p=0.019 and 0.011 respectively). Conclusion: Both of low dose (150 mg/kg BW) and high dose (300mg/kg BW) of borax exposure for 8 weeks cause microscopic gastric ulcer on rats.